GAMBARAN PERILAKU FIVE MOMENT HAND HYGIENE PERAWAT DI INSTALASI GAWAT DARURAT RUMAH SAKIT X - Hadi Nugroho; Esti Eka Sari M; Oryza Intan Suri; Dewi Anggraini (Jurnal Kesehatan STIKes IMC Bintaro, 2022)
Introduction : HAIs are one of the main causes of high morbidity and mortality rates in the worldwith 1.4 million deaths worldwide (WHO, 2014). Hand hygiene is an easy and important routine in infection control procedures and is the best method to preventmicroorganisms (James, 2016). The purpose of this study was to determine the Behavior Description of the Five Moment Hand Hygiene X in West Jakarta.Analytical descriptive research methodology with a survey method that aims to describe the five moment hand hygiene behavior of emergency room nurses at X Hospital, West Jakarta in 2020. The population of IGD nurses at X Hospital West Jakarta is 68 nurses, the sample used is 58 respondents. The research instrument used a questionnaire via google form. Data processing using SPPS with univariateanalysis. The results of the study were more age in 20-45 years, education with themost D3 Kep as many as 55 respondents, working period> 2 years at most as manyas 49 respondents, good knowledge as many as 29 respondents, positive attitude asmany as 34 respondents, good behavior as many as 40 respondents. Conclusion, the description of the behavior of five moment hand hygiene in ER RS X is good. Suggestions are that the emergency room nurses at X Hospital can continue to implement the five moment hand hygiene behavior so that nosocomial infections donot occur.